Free‐electron laser multiplex driven by a superconducting linear accelerator. (22nd July 2016) - Plath, Tim; Amstutz, Philipp; Bödewadt, Jörn; Brenner, Günter; Ekanayake, Nagitha; Faatz, Bart; Hacker, Kirsten; Honkavaara, Katja; Lazzarino, Leslie Lamberto; Lechner, Christoph; Maltezopoulos, Theophilos; Scholz, Matthias; et al.
Abstract : The first simultaneous lasing of three different free‐electron lasers driven by the same superconducting linear accelerator at FLASH at DESY is presented. Abstract : Free‐electron lasers (FELs) generate femtosecond XUV and X‐ray pulses at peak powers in the gigawatt range. The FEL user facility FLASH at DESY (Hamburg, Germany) is driven by a superconducting linear accelerator with up to 8000 pulses per second. Since 2014, two parallel undulator beamlines, FLASH1 and FLASH2, have been in operation. In addition to the main undulator, the FLASH1 beamline is equipped with an undulator section, sFLASH, dedicated to research and development of fully coherent extreme ultraviolet photon pulses using external seed lasers. In this contribution, the first simultaneous lasing of the three FELs at 13.4 nm, 20 nm and 38.8 nm is presented.